Hamsters, gerbils, guinea pigs, pet mice, & pet rats - Hahn, James; Hahn, Lynn (New York : F. Watts, 1977)
General information on the history of these rodents and instructions for raising them as pets.
Includes index.
Keywords: Rodents as pets -- Juvenile literature; Rodents as pets; Pets